Synthesis and characterization of block copolymer and comparative study with random copolymer via superacid–catalyzed reaction. (28th June 2018) - Ryu, Taewook; Ahmed, Faiz; Sutradhar, Sabuj Chandra; Lopa, Nasrin Siraj; Yang, Hanmo; Yoon, Soojin; Lee, Seungchan; Choi, Inhwan; Kim, Whangi
Abstract: The grafted block copolymer based polymer electrolyte membrane (PEM) was successfully synthesized by the superacid-catalyzed polyhydroxyalkylation reaction from biphenyl, 2, 2′-biphenol and isatin and the performance of the block copolymer were compared in conjunction with the random copolymer. These polymers have all carbon-carbon structure on polymer backbone without ether linkage. The bromoalkylsulfone potassium salt was prepared from 1, 3-propane sultone and potassium bromide. Particularly, the attached alkyl sulfone groups were afforded better stability due to less reactivity towards nucleophilic substitution reaction. Moreover, the block copolymer exhibited better proton conductivity (76.84 mS/cm under 90% relative humidity at 80  ° C), water resistivity, chemical, and thermal stability compared to the random copolymer, because block copolymer membranes showed good hydrophilic/hydrophobic phase separation and wide ionic channels. The structures of the resultant PEMs were confirmed by 1 H NMR spectroscopy and thermogravimetric analysis (TGA). These membranes were studied by proton conductivity, water uptake (WU), and ion exchange capacity (IEC). Fenton test was attended by Fenton's reagent (4 ppm Fe 2+, 3% H2 O2 ) for confirmation of the polymer degradation and the surface morphology of membranes was also analyzed by atomic force microscope. Highlights: The grafted block copolymer was synthesized via super acid catalyzed reaction. The properties of the block copolymer were compared in conjunction with random copolymer. Block copolymer exhibited better cell performance compared to random copolymer. Grafted block copolymer showed 18.75% water uptake.